2020
DOI: 10.3390/s20185021
|View full text |Cite
|
Sign up to set email alerts
|

Estimation Method of Soluble Solid Content in Peach Based on Deep Features of Hyperspectral Imagery

Abstract: Soluble solids content (SSC) is one of the important components for evaluating fruit quality. The rapid development of hyperspectral imagery provides an efficient method for non-destructive detection of SSC. Previous studies have shown that the internal quality evaluation of fruits based on spectral information features achieves better results. However, the lack of comprehensive features limits the accurate estimation of fruit quality. Therefore, the deep learning theory is applied to the estimation of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The results showed that SAE-PLSR model had the best prediction results, r and root mean square error (RMSE) of prediction set were 0.938 and 0.654 respectively. With the improvement of deep learning theory, Yang et al introduced deep learning theory into the prediction of SSC content of peach, and proposed a SSC estimation method of fresh peach based on deep features of hyperspectral image fusion information (Yang et al, 2020). The distance from the peach sample to the lens is 220 mm, the wavelength range is 900-1740 nm, and the spectral resolution is 5 nm.…”
Section: Fruit Maturity and Biochemical Parameters Detection Based On...mentioning
confidence: 99%
“…The results showed that SAE-PLSR model had the best prediction results, r and root mean square error (RMSE) of prediction set were 0.938 and 0.654 respectively. With the improvement of deep learning theory, Yang et al introduced deep learning theory into the prediction of SSC content of peach, and proposed a SSC estimation method of fresh peach based on deep features of hyperspectral image fusion information (Yang et al, 2020). The distance from the peach sample to the lens is 220 mm, the wavelength range is 900-1740 nm, and the spectral resolution is 5 nm.…”
Section: Fruit Maturity and Biochemical Parameters Detection Based On...mentioning
confidence: 99%
“…Another significant factor, where HSI systems proved not only to detect nonobvious bruises of fruits but also capable of assessing internal quality parameters such as soluble solid content, firmness, pH value, antioxidant, etc. [161][162][163][164][165][166][167][168][169][170][171].…”
Section: Illustrated Traditional Measuring Technique (A) and (B) Nir-hsi (1) Single Band At 1450 Nm (2) Binary Image Obtained Indicating mentioning
confidence: 99%
“…Xu extracted the deep features of the spectrum to improve the detection of different types of Pu’er tea [ 27 ]. Yang et al designed different structures of stacked autoencoder (SAE) to extract the deep features of hyperspectral images, which improved the accuracy of the estimation of soluble solid content in peach [ 28 ]. The research mentioned above showed that deep features could effectively improve the classification, recognition, and prediction of target objects.…”
Section: Introductionmentioning
confidence: 99%